2017
DOI: 10.1101/178673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and kinetics characterization of a wax ester hydrolase from a feather-degrading actinomycete

Abstract: Streptomyces fradiae var. k11 is a Gram-positive soil microorganism capable of degrading chicken feathers. Apart from being mostly protein, chicken feathers have a considerable level of lipids, with wax esters being the largest lipid class. The waxes may pose a challenge while rendering the feathers into coproducts, such as feather meal, and so the identification of a wax-ester hydrolase is warranted. A draft genome sequence of S. fradiae var. k11 was used to identify 14 gene sequences of potential lipid-degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…While we have previously shown that the TTF of a biodegradable soil moisture sensor coated in a single weight ratio of 25% soy in beeswax can be modulated by varying the coating thickness, here we also show that failure time can also be tuned by varying the weight ratio of soy wax in beeswax. The degradation of wax esters, n -alkanes, and fatty acids depends on the microbiome of the soil, ,, making blends of waxes such as beeswax and soy wax useful candidates for a biodegradable encapsulant. The type of soy wax used in this study, PHSBO, has been reported in prior studies to comprise unsaturated fatty acids, all of which are known to degrade relatively rapidly in soil .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we have previously shown that the TTF of a biodegradable soil moisture sensor coated in a single weight ratio of 25% soy in beeswax can be modulated by varying the coating thickness, here we also show that failure time can also be tuned by varying the weight ratio of soy wax in beeswax. The degradation of wax esters, n -alkanes, and fatty acids depends on the microbiome of the soil, ,, making blends of waxes such as beeswax and soy wax useful candidates for a biodegradable encapsulant. The type of soy wax used in this study, PHSBO, has been reported in prior studies to comprise unsaturated fatty acids, all of which are known to degrade relatively rapidly in soil .…”
Section: Resultsmentioning
confidence: 99%
“…Beeswax is composed primarily of wax esters, followed by hydrocarbons, and then by fatty acids. Degradation of beeswax in soil has previously been investigated in the context of historical artifact and art preservation. Due to the complex composition of beeswax, several modes of degradation have been hypothesized to explain the deterioration of both beeswax artifacts themselves and beeswax used to preserve damaged pieces. Wax ester hydrolases, especially SFK3309, have been identified in soils and have been shown to hydrolyze wax esters in beeswax . Palmitic acid results from the hydrolysis of wax esters, which could then sublimate or possibly form salts which would dissolve into groundwater, especially in alkaline or saline soils .…”
Section: Introductionmentioning
confidence: 99%
“…This feature also aids in thermoregulation, as it keeps water away from the skin. In addition, this oil can prevent feathers from being damaged by parasitic microorganisms ( Barcus et al., 2017 ). Preen gland also plays very important roles in the adaptation of stress and other biochemical processes ( Moreno-Rueda, 2017 ).…”
Section: Discussionmentioning
confidence: 99%